Comparative Genome Analyses of Wild Type- and Quinolone Resistant Escherichia coli Indicate Dissemination of QREC in the Norwegian Broiler Breeding Pyramid - Kaspersen, Håkon; Fiskebeck, Eve Zeyl; Sekse, Camilla; Slettemeås, Jannice Schau; Urdahl, Anne Margrete; Norström, Madelaine; Lagesen, Karin; Simm, Roger (Frontiers in Microbiology, 2020)
Quinolones are important antimicrobials for both humans and animals, and resistance towards these compounds is a serious threat to public health. In Norway, quinolone resistant E. coli (QREC) have been detected at low levels in a high proportion of broiler flocks, even without the use of quinolones in rearing of broilers. Due to the pyramidal structure of broiler breeding, QREC isolates may be disseminated from grandparent animals down through the pyramid. However, quinolone resistance can also develop in wild type E. coli through specific chromosomal mutations, and by horizontal acquisition of plasmid-mediated quinolone resistance genes. The goal of this study was to determine whether QREC is disseminated through the broiler breeding pyramid or developed locally at some stage in the broiler production chain. For this purpose, we whole genome sequenced wild type- and QREC isolates from broiler and parent flocks that had been isolated in the Norwegian monitoring program for antimicrobial resistance in feed, food and animals (NORM-VET) between 2006 and 2017, from 22 different production sites. The sequencing data was used for typing of the isolates, phylogenetic analysis and identification of relevant resistance mechanisms. Highly similar QREC isolates were identified within major sequence types from multiple production sites, suggesting dissemination of QREC isolates in the broiler production chain. The occurrence of potential resistance development among the WT E. coli was low, indicating that this may be a rare phenomenon in the Norwegian broiler production. The results indicate that the majority of the observed QREC at the bottom of the broiler production pyramid originates from parent or grandparent animals. These results highlight the importance of surveillance at all levels of the broiler production pyramid and of implementation of proper biosecurity measures to control dissemination of QREC.